Gunslinger spawn (2021), volume 5 ebook - McFarlane, Todd (Gunslinger Spawn (2021), 2024)
Gunslinger GOES TO HELL! Instead of seeking revenge, he is asked for help by an unexpected adversary, and accepts the challenge to defeat SINN, an unbeatable man, and gets caught up in the dangerous race for the Throne of Hell, which might offer him a means to return home. In the aftermath of SPAWN #350, danger looms for everyone, and Gunslinger, wounded and fleeing, finds assistance from an unlikely source. Collects GUNSLINGER SPAWN Issues #25-30